Pengaruh Penggunaan Media Pembelajaran Interaktif Berbantuan Android Terhadap Hasil Belajar pada Mata Pelajaran IPS Kelas VIII MTs Al-Huda Pekanbaru - Attifa, Fadlulrahman; Yeni J, Fetri; Novrianti, Novrianti; Amsal, Mutiara Felicita (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to assess the significant impact of the use of Android-assisted interactive learning media on student learning outcomes in social studies grade VIII at MTs Al Huda Pekanbaru. The research method used is the quasi-experimental method. The instrument used is a test to see student learning outcomes. The resulting data is statistically tested and analyzed descriptively. Based on the research conducted, it was found that the use of interactive learning media assisted by Android had a positive impact on students' academic achievement. The average score in the experimental class was proven to be higher compared to the average score in the control class, with the experimental class achieving an average score of 74.54, while the control class had an average score of 63.63. Based on the t-test results, the calculated t-value was 2.31, while the t-tabel value at a significance level of 0.05 was 2.018. Since the calculated t-value (2.31) is greater than the t-tabel value (2.018), it can be concluded that H1 is accepted. In conclusion, the use of interactive learning media assisted by Android has a significant impact on the learning outcomes of eighth-grade social studies students at MTs Al Huda Pekanbaru